Effect of Antibodies Against Intercellular Adhesion Molecule-1, B7, and CD40 on Interleukin-18-Treated Human Mixed Lymphocyte Reaction - Hideo Kohka Takahashi; Hiromi Iwagaki; Ryuji Tamura; Takahito Yagi; Tadashi Yoshino; Shuji Mori; Noriaki Tanaka; Masahiro Nishibori (Elsevier, 2005)
The interleukin (IL)-18 level in plasma is elevated during the acute rejection after organ transplantation. IL-18 elicits adhesion molecule expression as well as interferon-γ/IL-12 production and T-cell proliferation in the human mixed lymphocyte reaction, an in vitro model of acute rejection. We examined whether antibodies (Abs) against intercellular adhesion molecule (ICAM)-1, B7, CD40, and CD40, ligand (CD40L) affect the cytokine production and T-cell proliferation. Anti-ICAM-1 and B7 Abs suppressed the cytokine production, while all Abs inhibited T-cell proliferation. ICAM-1 and B7 as well as CD40 may play different roles in the acute rejection. Keywords:: interleukin-18, mixed lymphocyte reaction, adhesion molecule